Pengaruh Ekstrak Daun Mangrove (Avicennia marina) terhadap Ketahanan Tubuh Udang Vaname (Litopenaeus vannamei ) - Samuria, Sitti Asna; Nur, Indriyani; Hamzah, Muhaimin (Universitas Halu Oleo, 2018)
This study aims to determine the optimum dose of mangrove leaf extract (A. marina) which is able to improve the resistance of vaname shrimp (L. vannamei). The stages in this study consisted of : (1) extraction of mangrove leaves and, (2) Immunostimulation of shrimp with extracts orally, (3) analysis of shrimp resistance to defend against Vibrio alginolitycus bacterial infection through challange test. The treatment was conducted in different doses of extract in feed (10, 15, 20 g/kg), and the control treatment was pellets without extract. Feeding with the addition of the extract was carried out for 40 days, then tested against the bacterium V.alginolitycus. The parameter observed in this study was Survival Rate (SR) and clinical signs. In the treatment of 20 g showed an optimal increase in the vaname shrimp immune response with significantly different result compared to other treatments. Keywords : Vannamei, Mangrove Leaves, V. alginolyticus, Immunity